The Premia on State-Contingent Sovereign Debt Instruments - Igan, Deniz; Kim, Taehoon; Levy, Antoine (Washington, D.C. : International Monetary Fund, 2021)
State-contingent debt instruments such as GDP-linked warrants have garnered attention as a potential tool to help debt-stressed economies smooth repayments over business cycles, yet very few studies of the empirical properties of these instruments exist. This paper develops a general f ramework to estimate the time-varying risk premium of a state-contingent sovereign debt instrument. Our estimation framework applied to GDP-linked warrants issued by Argentina, Greece, and Ukraine reveals three stylized facts: (i) the risk premium in state-contingent instruments is high and persistent; (ii) the risk premium exhibits a pro-cyclical pattern; and (iii) the liquidity premium is higher and more volatile than that for plain-vanilla government bonds issued by the same sovereign. We then present a model in which investors fear ambiguity and that can account for the cyclical properties of the risk premium.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Contingent Pricing; Debt Management; Debt; Futures Pricing; Sovereign Debt